The role of the microbiota in connective tissue diseases - Aleksandra Fijałkowska; Agnieszka Żebrowska (Termedia Publishing House, 2023)
Connective tissue diseases are a group of diseases with a complex etiology characterized by abnormal activity of the immune system. In the last decade, the role of the gut microbiota as a potential modulator of diseases such as systemic lupus erythematosus and systemic sclerosis has attracted significant interest. Deviations in the composition of the intestinal microbiota cause a number of unfavorable consequences that may lead to progression of connective tissue diseases. So far, there is no clear knowledge whether dysbiosis induces the development of these diseases or is a secondary phenomenon to pathological changes occurring in the body. Research is currently underway to develop innovative therapeutic strategies based on regulation of the composition of intestinal bacteria. This may allow limiting the use of basic immunosuppressive drugs associated with high risk of side effects.